2017
DOI: 10.1117/1.jmi.4.3.034006
|View full text |Cite
|
Sign up to set email alerts
|

Tracking and diameter estimation of retinal vessels using Gaussian process and Radon transform

Abstract: Abstract. Extraction of blood vessels in retinal images is an important step for computer-aided diagnosis of ophthalmic pathologies. We propose an approach for blood vessel tracking and diameter estimation. We hypothesize that the curvature and the diameter of blood vessels are Gaussian processes (GPs). Local Radon transform, which is robust against noise, is subsequently used to compute the features and train the GPs. By learning the kernelized covariance matrix from training data, vessel direction and its di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Analysis of tubular structures for biological applications plays crucial roles in diagnosing several pathologies such as cardiovascular disorders, diabetes, spinal stenosis, central retinal vein analysis, and hypertension [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. All of these applications would benefit from accurate and fast dimensioning for quicker diagnosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of tubular structures for biological applications plays crucial roles in diagnosing several pathologies such as cardiovascular disorders, diabetes, spinal stenosis, central retinal vein analysis, and hypertension [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. All of these applications would benefit from accurate and fast dimensioning for quicker diagnosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies model the vessels’ tortuosity by polynomial fitting techniques [ 1 , 31 , 32 ]. These algorithms increase the error in centreline estimation depending on the vessel’s complexity, reducing accuracy if used for diameter measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Important works have been developed in the retina [7] and coronary arteries [8], but a thorough search of relevant literature revealed that no work has been done so far in the automatic identification of perforators for microsurgery.…”
Section: Introductionmentioning
confidence: 99%
“…Unsupervised methods on the other hand does not need to have a prior training session, but use rule-based methods to identify vessel pixels against background pixels. Some of the available techniques include kernel-based method [3]- [5], vessel tracking method [6], [7], mathematical morphologybased method [8], [9], multi-scale method [10]- [12], machine learning method [13]- [16] and model-based method [17], [18]. B-COSFIRE, stands for Bar-selective Combination of Shifted Filter Responses, is an efficient method to segment RBV from digital fundus images [19].…”
Section: Introductionmentioning
confidence: 99%